Evaluasi Produksi Kaksa Dalam Upaya Pencapaian TargetPemindahan Tanah Bulanan Sebesar 30.000 m3 DI TB.2.1 Tempilang, PT Timah (Persero) Tbk: Evaluation of Kaksa Production in Efforts of 30.000 m3 Earthmoving Monthly Target Achievementsin TB.2.1 Tempilang, PT Timah (Persero) Tbk - Ramona, Pisca; Irvani, Irvani; Mardiah, Mardiah (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2017)
Earthmoving target of 30,000 m3 in TB.2.1 Tempilang reached in March where production amounted to 36.350 m3, but the decline occurred in April at 1,83% with amount of production is 29.450 m3 and in May 46% with amount of production is 16,200 m3. Evaluation was conducted against the data rate of excavation In March until May, 2016. Other than that, evaluation of factors of production activities the influential hearts with how to calculate productivity tool for the reviews to know the tool's ability to produce kaksa, reviewing data that stop-time increasing production, the rate of rainfall, and sediment property value with the observe incision drill profile block in March, April, and May 2016. Based on the findings of evaluation, main factors failure achievement of production is time road experienced a decline of 05 hours during the month of April and 138 hours In May due to damage to the equipment and high rainfall reached 332 mm. Monthly soil removal target can be achieved with change hours number: Available 8 hours / day Being 10 hours / day.